The reasons for changing HAART in HIV positive patients at the Thusong comprehensive care management and treatment site, West Rand district, Johannesburg, Gauteng - Imran, Syed Ali (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2011.